Fodder Production in Agrisilvicultural System under Rainfed Condition in Kashmir - Qaisar, K.N.; Khan, P.A.; Khan, M.A.; Zaffar, S.N.; Mughloo, Javed A. (Indian Journal of Agroforestry, 2020)
An experiment was conducted under rainfed conditions in Kashmir with two commonly planted species PopulusÂ deltoides and Catalpa bignoniodes with Kharif (Sorghum var. M.P.Chari) and Rabi (Oats var. Sabzar) fodder crops. TheÂ productivity of trees in combination of fodder crop was observed 85 and 87 per cent more in terms of tree fodder + fuelwood yield. The fodder crop yield was decreased in combination of trees+fodder crop compared to sole fodder crop. The land equivalent ratio of Populus + fodder crop was 2.72 and Catalpa + fodder crop was 2.77. The available nutrients (N, P, K) and soil microbial count were recorded higher in combination of tree + fodder crop.